Some Approaches To The Assessment of Over tourism in Mature Tourist Destinations - Dmitriy Valerievich Chigarev (Indonesian Journal of Law and Economics Review, 2020)
The purpose of the article is to analyze approaches to assessing this phenomenon in mature tourist destinations. The article gives a detailed analysis of some publications. The authors focus on five types of problems associated with it: alienated local residents, a degraded tourist experience, overloaded infrastructure, damage to nature, and threat to culture and heritage. Diagnostics was developed which allows determining the level of risk of overcrowding by tourists in destinations. Some shortcomings of this methodology were pointed out in a study conducted by a number of authors (Peeters et al., 2018) for the European Parliament Committee on Transport and Tourism. The study focuses on the main indicators of overtourism. For regions or destinations wishing to assess the risk of overtourism, a checklist has been proposed to evaluate it. The authors of the joint study by the Austrian Hotelier Association (ÖHV) and the Roland Berger global consultancy firm (2018) divided measures to combat overtourism into proactive measures (when destinations plan their activities) and reactive measures (when cities are already experiencing problems with overtourism). In addition, a four-step sustainable tourism development plan has been developed. All authors agree that the lack of reliable statistics makes it difficult to effectively identify the state of overtourism in destinations. Nevertheless, the planning and vigorous activity of all interested parties (business, government, society) will allow weakening the social, economic and environmental consequences of overtourism for mature tourist destinations.